Financing power: Impacts of energy policies in changing regulatory environments - Nils May; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Power systems with increasing shares of wind and solar power generation have higher capital and lower operational costs than traditional technologies. This increases the importance of the cost of finance for total system cost. We quantify how renewable policy design can influence cost of finance by addressing regulatory risk and facilitating hedging. We use interview data on wind power financing costs from the EU and model how long-term contracts signed between project developers and energy suppliers impact financing costs in the context of green certificate schemes. Be- tween the policy regimes, the cost of renewable energy deployment differ by 30%.
Keywords: Q42; Q55; O38; 330; Investments; Long-term contracts; Financing costs; Liberalization of power markets; Renewable energy policies